2016
DOI: 10.1007/s00726-016-2267-3
|View full text |Cite
|
Sign up to set email alerts
|

Cellular compartmentation of energy metabolism: creatine kinase microcompartments and recruitment of B-type creatine kinase to specific subcellular sites

Abstract: There is an increasing body of evidence for local circuits of ATP generation and consumption that are largely independent of global cellular ATP levels. These are mostly based on the formation of multiprotein(-lipid) complexes and diffusion limitations existing in cells at different levels of organization, e.g., due to the viscosity of the cytosolic medium, macromolecular crowding, multiple and bulky intracellular structures, or controlled permeability across membranes. Enzymes generating ATP or GTP are found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 189 publications
(211 reference statements)
1
56
0
Order By: Relevance
“…Phosphagens are prevalent in all species and play an important role in maintaining energy availability [1, 2, 24, 25]. The primary metabolic role of creatine is to combine with a phosphoryl group (Pi) to form PCr through the enzymatic reaction of creatine kinase (CK).…”
Section: Metabolic Rolementioning
confidence: 99%
See 2 more Smart Citations
“…Phosphagens are prevalent in all species and play an important role in maintaining energy availability [1, 2, 24, 25]. The primary metabolic role of creatine is to combine with a phosphoryl group (Pi) to form PCr through the enzymatic reaction of creatine kinase (CK).…”
Section: Metabolic Rolementioning
confidence: 99%
“…Wallimann and colleagues [26–28] suggested that the pleiotropic effects of Cr are mostly related to the functions of CK and PCr (i.e., CK/PCr system). As adenosine triphosphate (ATP) is degraded into adenosine diphosphate (ADP) and Pi to provide free energy for metabolic activity, the free energy released from the hydrolysis of PCr into Cr + Pi can be used as a buffer to resynthesize ATP [24, 25]. This helps maintain ATP availability particularly during maximal effort anaerobic sprint-type exercise.…”
Section: Metabolic Rolementioning
confidence: 99%
See 1 more Smart Citation
“…Besides oxidative phosphorylation, creatine kinase (CK) is also a key player in maintaining cellular energy homeostasis in many metabolically demanding tissues including muscle and brain (57). CK uses creatine (Cr) for reversible phosphoryl transfer between ATP and PCr in the following reaction:…”
Section: Energy Metabolism In Living Tissuesmentioning
confidence: 99%
“…Using sophisticated membrane and vesicle isolation procedures and yeast two-hybrid analysis suited to identify membrane proteins as interaction partners, Schlattner et al (2016) identified a number of membrane proteins of the brain associated with brain-type cytosolic BB-CK. These novel micro-compartments of BB-CK with, for example, VAMP2 proteins and JWA, shed new light on synaptic functions dependent on BB-CK-mediated energy provision.…”
Section: Basic Science: Old and New Creatine Kinase Micro-compartmentsmentioning
confidence: 99%